Is Leptospira able to survive in raw milk? Study on the inactivation at different storage times and temperatures - Fratini, Filippo; Turchi, Barbara; Ferrone, Martina; Galiero, Alessia; Nuvoloni, Roberta; Torracca, Beatrice; Cerri, Domenico (Folia microbiologica, 2016)
The consumption of raw milk is currently increasing due to several beneficial aspects, such as nutritional qualities, taste, and health benefits. However, some authors highlight the potential risk associated with raw milk consumption. In Italy, while the absence of some pathogen microorganisms is set by the regional regulation DGR 381/2007, for other microorganisms, such as Leptospira, no recommendations are provided. Leptospira is not ascribed among classical milk pathogens; however, it can potentially be present in raw milk. The aim of this study was to evaluate the survival in raw milk of six serovars of Leptospira after storage at different temperatures (4 °C ± 2 °C, 20 °C ± 2 °C, and 30 °C ± 2 °C) for different incubation times (20 min, 45 min, 1 h, and 1 h and 30 min), in order to determine the potential risk for consumers. Moreover, the immediate effect of bovine, goat, and donkey raw milk on tested Leptospira serovars was visually evaluated. After incubation, all samples were subcultured in EMJH and incubated aerobically at 30 °C for 3 months. All inoculated media were weekly examined by dark-field microscope in order to assess Leptospira survival. Extemporary observation of strains' behavior in milk allowed to detect an almost immediate motility loss, and no leptospires were detected by microscopic observations carried out weekly during the trial period. According to our results, it could be possible to exclude raw milk as a source of Leptospira infection for consumers.
Keywords: Cattle; kozy; Temperature; bakteriologické techniky; mikrobiální viabilita; Leptospira; Goats; skot; skladování potravin; Itálie; Food Storage; Time Factors; Animals; Microbial Viability; Equidae; Aerobiosis; zvířata; mléko; časové faktory; teplota; Italy; aerobióza; Milk; Bacteriological Techniques